2011
DOI: 10.1155/2011/206756
|View full text |Cite
|
Sign up to set email alerts
|

Differential Signature of the Centrosomal MARK4 Isoforms in Glioma

Abstract: Abstract.Background: MAP/microtubule affinity-regulating kinase 4 (MARK4) is a serine-threonine kinase expressed in two spliced isoforms, MARK4L and MARK4S, of which MARK4L is a candidate for a role in neoplastic transformation.Methods: We performed mutation analysis to identify sequence alterations possibly affecting MARK4 expression. We then investigated the MARK4L and MARK4S expression profile in 21 glioma cell lines and 36 tissues of different malignancy grades, glioblastoma-derived cancer stem cells (GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Here, we used RNA-seq to identify the regulatory networks of mRNAs and noncoding RNAs in breast cancer. Among the results from the analysis of potential mRNA interactions, MARK4 sparked our interest since it is associated with tumorigenesis [49,50]. Previous studies showed that MARK4 attenuates the proliferation and migration of MDA-MB-231 cells via the Hippo signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used RNA-seq to identify the regulatory networks of mRNAs and noncoding RNAs in breast cancer. Among the results from the analysis of potential mRNA interactions, MARK4 sparked our interest since it is associated with tumorigenesis [49,50]. Previous studies showed that MARK4 attenuates the proliferation and migration of MDA-MB-231 cells via the Hippo signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that Par-1 may have a procarcinogenic role because its hyperactivation in Drosophila is sufficient to induce tissue overgrowth, and in mammals, Par-1 is sufficient to activate YAP. Interestingly, MARK4 has been suggested to play a role in hepatocellular carcinogenesis and gliomagenesis [51],[52]. However, whether MARK1 is also involved in carcinogenesis is largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Hyper-phosphorylation of the microtubule-associated protein Tau by microtubule affinity regulating kinase, the homolog of Drosophila Par-1 (MARK) [48], which is activated by upstream kinases, such as LKB1 [49] and Tao-1 [50], results in microtubule depolymerization and abnormal aggregation of Tau in Alzheimer disease. Additionally, MARK4 has been reported to be involved in hepatocellular carcinogenesis and gliomagenesis [51],[52].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite their common occurrence, and perhaps due to the heterogeneity of centrosome abnormalities in cancer, it has been difficult to determine whether centrosomes abnormalities are caused by primary intrinsic centrosome defects, or are the consequence of dysfunction of other cellular processes that lead to the accumulation of normally replicated centrosomes, such as for instance in cases of cell division failure ( 271 , 272 ). In consequence a considerable volume of ongoing research is being devoted to elucidating in detail the molecular pathways involved in centrosome dysfunction in cancer, their impact on the cancer genome, and the prospects of utilizing centrosome defects as biomarkers ( 205 , 273 , 274 ) and targets for cancer specific therapy ( 275 279 ).…”
Section: Abnormal Centrosomes In Cancermentioning
confidence: 99%